Patient's Attitudes Towards the Use of Complementary and Alternative Medicine in Finland: an Ethnomedical Insight Based on Cancer Narratives - Piret Paal (Journal of Ethnology and Folkloristics)
As in many other countries, the second half of the 19th century and the first half of the 20th century marked times of modernisation in Finland. Rapid changes also took place in the health care system at this time. Until the 1920s most health concerns were addressed using the ethnomedical practices. New legislation gave the dominant position in health care to the Western (evidence based) health care system. According to the official record, the majority of ethnomedical treatments were declared marginal and generally useless and the state began to support the construction of hospitals. The slow pace of development in social health care held up the treatments given by legally approved medical practitioners. All of which supported a deliberate shift towards the modernisation of the health care system leading to primary health concerns being solved in local health care centres by doctors trained according to the conventions of evidence based medicine. Unlike many other countries, where the representatives of conventional medicine also consider complementary and alternative medicine as a part of their treatment, the use of non-evidence based medicine is extremely unusual in Finland. However, patients with long-term illnesses are eager to try all available cures in their desire to become well and this leads to a situation in which complementary treatments are used in a somewhat secretive manner. The article follows the discussion concerning the use of complementary and alternative medicine in cancer narratives in order to point out its significance as a part of a self-negotiation process characteristic to the patients with long-term illnesses.